GENERAL AND SPECIAL SPORTS TRAINING OF WRESTLERS - Yusupov Erali To‘ychiyevich (Bright Mind Publishing, 2025)
This article provides a brief overview of the general and special sports training of wrestlers.
Keywords: Wrestling, training, sport, form, skill, technique, tactics, result.